Upaya Peningkatan Hasil Belajar Pendidikan Agama Islam melalui Metode Peer Group Teaching pada Siswa Sekolah Menengah Pertama - Misran Misran; Kasmantoni Kasmantoni (Jurnal Indonesia Kajian Pendidikan Islam, 2025)
Background: Low student learning outcomes in Islamic education are often attributed to traditional teaching methods that fail to actively engage students. Implementing interactive methods, such as Peer Group Teaching (peer tutoring), is expected to enhance student participation and mastery of Islamic education material. Objective: This study aims to evaluate the implementation of the Peer Group Teaching (peer tutoring) method in Islamic education subjects for Class VII students at SMPN 29 Oku and assess its impact on improving student learning outcomes. Method: This research adopted a Classroom Action Research (CAR) design, which included three cycles: pre-cycle, Cycle I, and Cycle II. Each cycle involved planning, action implementation, observation, and analysis-reflection stages. The research subjects were Class VII students, and data were collected through competency tests and observations of group learning activities. Results: The findings indicate that the use of the Peer Group Teaching (peer tutoring) method improved student learning outcomes. Out of 30 students, 26 (87%) met the minimum competency criteria (KKM) of 77, surpassing the success indicator of 80%. However, 4 students (13%) had not yet achieved individual mastery. Conclusion: The Peer Group Teaching method is effective in enhancing Islamic education learning outcomes and fostering active student participation. Contribution: This study offers practical guidance for teachers on implementing peer-assisted learning to improve student engagement and achievement in Islamic education subjects.